2014
DOI: 10.1363/46e0414
|View full text |Cite
|
Sign up to set email alerts
|

Abortion Incidence and Service Availability In the United States, 2011

Abstract: CONTEXT-National and state-level information about abortion incidence can help inform policies and programs intended to reduce levels of unintended pregnancy. [2015][2016], all U.S. facilities known or expected to have provided abortion services in 2013 or 2014 were surveyed. Data on the number of abortions were combined with population data to estimate national and state-level abortion rates. The number of abortionproviding facilities and changes since a similar 2011 survey were also assessed. The number and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
422
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(426 citation statements)
references
References 32 publications
1
422
1
2
Order By: Relevance
“…First, because reporting requirements are established by the individual reporting areas (21), the collection of data varies and CDC is unable to obtain the total number of abortions performed in the United States. During the period covered by this report, the total annual number of abortions reported to CDC was consistently approximately 70% of the number recorded by the Guttmacher Institute (15,67), which uses numerous active follow-up techniques to increase the completeness of the data obtained through its periodic national census of abortion providers (15). Although most reporting areas collect and send abortion data to CDC, this information is submitted to CDC voluntarily.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, because reporting requirements are established by the individual reporting areas (21), the collection of data varies and CDC is unable to obtain the total number of abortions performed in the United States. During the period covered by this report, the total annual number of abortions reported to CDC was consistently approximately 70% of the number recorded by the Guttmacher Institute (15,67), which uses numerous active follow-up techniques to increase the completeness of the data obtained through its periodic national census of abortion providers (15). Although most reporting areas collect and send abortion data to CDC, this information is submitted to CDC voluntarily.…”
Section: Limitationsmentioning
confidence: 99%
“…For 1998-2012, abortion surveillance data reported to CDC cannot be used alone to calculate national case-fatality rates (number of legal induced abortion-related deaths per 100,000 reported legal induced abortions in the United States) because certain states § § did not report abortion data every year during this period. Thus, national legal induced abortion case-fatality rates were calculated with denominator data from a more complete source on the total number of abortions performed in the United States (15). Because rates determined on the basis of a numerator of <20 deaths are highly variable (38), national legal induced abortion case-fatality rates were calculated for consecutive 5-year periods during 1973-2012.…”
Section: Abortion Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to the demographic and health survey in Turkey, the rate of abortion among ever married women were 21%. 13 Jones and Jerman 14 conducted a study to determine abortion incidence and service availability in the United States indicated that the abortion ratio was 21% among women aged 15-44 in 2011. Moreover, the rate of abortion in Russia was found to be 38.5% in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…A group of women have severe and intolerable abortion pain however the pain can control easily in medical abortion during first and second-trimester of the pregnancy. In US the abortion rate is estimated approximately 1.1 million in 2011 and 2.8 -2.9% of 15-44 years old women have applied abortion worldwide each year between 2003 and 2008 [7,8]. It is estimated that 43% of American women experience at least one abortion in the childbearing age [9].…”
Section: Introductionmentioning
confidence: 99%